2019
DOI: 10.3389/fpsyg.2019.01621
|View full text |Cite
|
Sign up to set email alerts
|

Do Cross-National and Ethnic Group Bullying Comparisons Represent Reality? Testing Instruments for Structural Equivalence and Structural Isomorphism

Abstract: Bullying in schools is a widespread phenomenon, witnessed worldwide, with negative consequences for victims and perpetrators. Although it is an international issue, there are several issues with cross-national and cross-cultural/ethnic research that can make comparisons between countries and cultures/ethnic groups difficult including language, cultural perception, and/or methodological issues. As statistical techniques rapidly develop, there may be more scope to be statistically creative in how we assess the u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Therefore, there is also a need for studies in multiple countries, particularly in developing countries. This is important as different countries and cultures deal and define bullying and victimisation differently [ 91 , 92 ] and have different educational, school and grading systems, and thus interventions may differ in each country accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is also a need for studies in multiple countries, particularly in developing countries. This is important as different countries and cultures deal and define bullying and victimisation differently [ 91 , 92 ] and have different educational, school and grading systems, and thus interventions may differ in each country accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The process of coding and grouping of related terms is a key factor in a meta-analysis. Studies usually differ slightly in terminology and methodologies [ 91 , 92 ]; nevertheless, groups need to be formed, in order to study them in a meta-analysis. Vast methodological differences between cognitive–motivational factors were also observed.…”
Section: Discussionmentioning
confidence: 99%
“…54 A challenge in examining the effects of adversity on development is how to compare children growing up in different cultures. For example, one study 58 reported that a questionnaire on bullying used in different cultures and countries did not generalize well (eg, how one culture interpreted bullying differed from another). Adversity and trauma should be considered in context, and investigators in different cultures may need to develop different assessments.…”
Section: Recommendations For Researchmentioning
confidence: 99%
“…Other common issues, which are out of the scope this review, are (a) whether bullying/victimisation is measured by one, few or more items, and (b) whether measurement invariance across groups (grouped as age, gender, ethnicity/race, sexuality, disability, speciality, socioeconomic status, country or religion) is estimated. All these limitations yield inconsistent findings about percentages and characteristics of bullies and victims across different ethnicities and countries (Kisfalusi et al, 2020;Rodríguez-Hidalgo et al, 2019;Samara et al, 2019;Tolsma et al, 2013).…”
Section: Measurement Issues: Suggestions For Further Researchmentioning
confidence: 99%